Integrating Technology and Legal Strategies to Combat Evolving Money Laundering Tactics - Hananto, Andhika Rafi (International Journal of Informatics and Information Systems, 2022)
Money laundering has significantly advanced with the aid of technology, enabling perpetrators to exploit technological tools for criminal ease. This trend is compounded by the use of cross-border cash couriers, increasingly favored as a method for laundering illicit funds. International conventions and multilateral agreements acknowledge the vulnerability of cash courier operations to money laundering, yet current frameworks primarily offer detection guidelines rather than precise methods for direct recognition. Given that money laundering involves proceeds of crime, authorities must scrutinize and assess transactions to determine if criminal activity constitutes money laundering, distinct from customs violations.Moreover, the proliferation of innovative financial products and payment systems, including cryptocurrencies like Bitcoin, Litecoin, and other virtual currencies, as well as bearer negotiable instruments, has further facilitated money laundering opportunities. Research indicates that criminal tactics are outpacing legal frameworks, with technology infiltrating the strategies of money launderers and potentially overshadowing regulatory controls. Despite technology's neutral intent, its misuse challenges the traditional role of law enforcement.This qualitative study aims to analyze how legal frameworks can collaborate with technology to combat money laundering effectively. The hypothesis posits that the law can provide crucial guidance amid technological developments, while technology can prompt legal systems to adapt swiftly. By integrating these approaches, the research suggests that combating the evolution of money laundering becomes more formidable when law and technology converge.